Single muscle fibre contractile properties differ between body-builders, power athletes and control subjects - Meijer, J. P.; Jaspers, R. T.; Rittweger, J.; Seynnes, O. R.; Kamandulis, S.; Brazaitis, M.; Skurvydas, A.; Pisot, R.; Simunic, B.; Narici, M. V.; Degens, H. (Experimental Physiology, 2015)
We compared muscle fibre contractile properties of biopsies taken from the vastus lateralis of 12 body-builders (BBs; low- to moderate-intensity high-volume resistance training), six power athletes (PAs; high-intensity, low-volume combined with aerobic training) and 14 control subjects (Cs). Maximal isotonic contractions were performed in single muscle fibres, typed with SDS-PAGE. Fibre cross-sectional area was 67 and 88% (P < 0.01) larger in BBs than in PAs and Cs, respectively, with no significant difference in fibre cross-sectional area between PAs and Cs. Fibres of BBs and PAs developed a higher maximal isometric tension (32 and 50%, respectively, P < 0.01) than those of Cs. The specific tension of BB fibres was 62 and 41% lower than that of PA and C fibres (P < 0.05), respectively. Irrespective of fibre type, the peak power (PP) of PA fibres was 58% higher than that of BB fibres (P < 0.05), whereas BB fibres, despite considerable hypertrophy, had similar PP to the C fibres. This work suggests that high-intensity, low-volume resistance training with aerobic exercise improves PP, while low- to moderate-intensity high-volume resistance training does not affect PP and results in a reduction in specific tension. We postulate that the decrease in specific tension is caused by differences in myofibrillar density and/or post-translational modifications of contractile proteins.